Det dunkle namneleddet "Smør-" - Myrvang, Finn (NAMN OG NEMNE, 2022)
Scandinavian PN scholars have been a bit puzzled by the place-name word Smør-, that seems to indicate butter wasn’t only a commodity, but also a measure of prosperity and abundance at weddings etc. One of them was Kåre Hoel, who published a review in 1984 of Norwegian place-names with respect to Smør-, and in particular linked its importance to another factor, citing numerous older references where he concluded that many of them are tokens of good soil and crops, as well as excellent pastures and general wellbeing. The author of this article doesn’t disagree, but is of the opinion that a Norwegian equivalent of the Danish nomen smøre (Ê»scratch, cut, hurt etc.Ê¼) in many cases is a more likely explanation; in particular with reference to those uninhabited mountain regions and the barren rocks and inlets along the coast. It is also the case that Smør-names are so numerous that it’s improbable that they all refer to butter, some topographic place-name element seems to be involved. This is the main theme and provides important additional information when combined with ortho photos etc.